A Single‐Nucleotide Mutation in a GLUTAMATE RECEPTOR‐LIKE Gene Confers Resistance to Fusarium Wilt in Gossypium hirsutum. Issue 7 (19th February 2021) - Liu, Shiming; Zhang, Xiaojun; Xiao, Shenghua; Ma, Jun; Shi, Weijun; Qin, Tao; Xi, Hui; Nie, Xinhui; You, Chunyuan; Xu, Zheng; Wang, Tianyi; Wang, Yujing; et al.
Abstract: Fusarium wilt (FW) disease of cotton, caused by the fungus Fusarium oxysporum f. sp. vasinfectum ( Fov ), causes severe losses in cotton production worldwide. Though significant advancements have been made in development of FW‐resistant Upland cotton ( Gossypium hirsutum ) in resistance screening programs, the precise resistance genes and the corresponding molecular mechanisms for resistance to Fov remain unclear. Herein it is reported that Fov7, a gene unlike canonical plant disease‐resistance ( R ) genes, putatively encoding a GLUTAMATE RECEPTOR‐LIKE (GLR) protein, confers resistance to Fov race 7 in Upland cotton. A single nucleotide polymorphism (SNP) (C/A) in GhGLR4.8, resulting in an amino acid change (L/I), is associated with Fov resistance. A PCR‐based DNA marker ( GhGLR4.8 SNP(A/C) ) is developed and shown to cosegregate with the Fov resistance. CRISPR/Cas9‐mediated knockout of Fov7 results in cotton lines extremely susceptible to Fov race 7 with a loss of the ability to induce calcium influx in response to total secreted proteins (SEPs) of Fov . Furthermore, coinfiltration of SEPs with GhGLR4.8 A results in a hypersensitive response. This first report of a GLR‐encoding gene that functions as an R gene provides a new insight into plant–pathogen interactions and a new handle to develop cotton cultivars with resistance to Fov race 7. Abstract : Fusarium oxysporum f. sp. vasinfectum ( Fov ) is a widely distributed fungal pathogen seriously threatening cotton production. Herein, a GLUTAMATE RECEPTOR‐LIKE gene ( GhGLR4.8 ) is identified as an atypical disease‐resistance gene specifying resistance to Fov race 7 through a genome‐wide association study in upland cotton, which provides a new insight into plant–pathogen interactions and facilitates the development of elite Fov ‐resistant cultivars.